Young people's aspirations for education, work, family and leisure - McDonald, P.; Pini, Barbara; Bailey, J.; Price, R. (Sage Publications, 2011)
Young people are arguably facing more ‘complex and contested’ transitions to adulthood and an increasing array of ‘non-linear’ paths. Education and training have been extended, identity is increasingly shaped through leisure and consumerism and youth must navigate their life trajectories in highly individualised ways. The study utilises 819 short essays compiled by students aged 14–16 years from 19 schools in Australia. It examines how young people understand their own unique positions and the possibilities open to them through their aspirations and future orientations to employment and family life. These young people do not anticipate postponing work identities, but rather embrace post-school options such as gaining qualifications, work experience and achieving financial security. Boys expected a distant involvement in family life secondary to participation in paid work. In contrast, around half the girls simultaneously expected a future involving primary care-giving and an autonomous, independent career, suggesting attempts to remake gendered inequalities.